Agreement of BNP and NT-proBNP and the influence of clinical and laboratory variables - Curiati, Milena Novaes Cardoso (Einstein (Sao Paulo), 2013)
OBJECTIVE: To correlate the serum levels of B type natriuretic peptide and the N-terminal fraction of the pro-B type natriuretic peptide, as well as to analyze the influence of age, obesity, renal failure, left ventricle ejection fraction, diastolic dysfunction, and anemia on serum levels of both markers. METHODS: An observational study in which the agreement was compared between these markers in consecutive samples of 138 patients. For the correlation, Pearson's test was used, and p<0.05 was considered statistically significant. RESULTS: A linear association was observed between the B type natriuretic peptide and N-terminal fraction of the pro-B type natriuretic peptide (r = 0.907; p<0.001). When evaluating the categorized measurements as normal and altered, there was good agreement, with 90.6% of agreement classifications (p<0.001) in which altered values of the N-terminal fraction of the pro-B type natriuretic peptide and normal values of the B type natriuretic peptide represented 8.7% of the total; the opposite situation represented 1% of the total. Assessment of the influence of the clinical and laboratorial factors on the levels of natriuretic peptides showed that they rise according to age, but that they fall as the ejection fraction increases. Patients with anemia (p<0.001) or with renal failure (p=0.007) had higher values of both markers. There was no association between obesity and the B type natriuretic peptide. CONCLUSION: There was satisfactory agreement between the B type natriuretic peptide and the N-terminal fraction of the pro-B type natriuretic peptide. Age, creatinine levels, and hemoglobin, as well as ventricular function, influence the serum levels of both natriuretic peptides.